Joint Fluid Proteome after Anterior Cruciate Ligament Rupture Reflects an Acute Posttraumatic Inflammatory and Chondrodegenerative State. (July 2020) - King, John D.; Rowland, Grant; Villasante Tezanos, Alejandro G.; Warwick, James; Kraus, Virginia B.; Lattermann, Christian; Jacobs, Cale A.
Objective: The purpose of this study was to evaluate changes in the synovial fluid proteome following acute anterior cruciate ligament (ACL) injury. Design: This study represents a secondary analysis of synovial fluid samples collected from the placebo group of a previous randomized trial. Arthrocentesis was performed twice on 6 patients with an isolated acute ACL tear at a mean of 6 and 14 days postinjury. Synovial fluid was analyzed by a highly multiplexed assay of 1129 proteins (SOMAscan version 3, SomaLogic, Inc., Boulder, CO). Pathway analysis using DAVID was performed; genes included met 3 criteria: significant change between the 2 study time points using a paired t test, significant change between the 2 study time points using a Mann-Whitney nonparametric test, and significant Benjamini post hoc analysis. Results: Fifteen analytes demonstrated significant increases between time points. Five of the 15 have been previously associated with the onset and/or severity of rheumatoid arthritis, including apoliopoprotein E and isoform E3, vascular cell adhesion protein 1, interleukin-34, and cell surface glycoprotein CD200 receptor 1. Chondrodegenerative enzymes and products of cartilage degeneration all increased over time following injury: MMP-1 ( P = 0.08, standardized response mean [SRM] = 1.00), MMP-3 ( P = 0.05, SRM = 0.90), ADAM12 ( P = 0.03, SRM = 1.31), aggrecan ( P = 0.08, SRM = 1.13), and CTX-II ( P = 0.07, SRM = 0.56). Notable pathways that were differentially expressed following injury were the cytokine-cytokine receptor interaction and osteoclast differentiation pathways. Conclusions: The proteomic results and pathway analysis demonstrated a pattern of cartilage degeneration, not only consistent with previous findings but also changes consistent with an inflammatory arthritogenic process post-ACL injury.